ANALISIS PRODUKTIVITAS TOWER CRANE (Studi Kasus Proyek Bintaro Jaya Xchange Tahap II, Tangerang Selatan) - galih wulandari subagyo; Ryan Tjondro (Universitas Trisakti, 2021)
In a construction project, tower crane productivity is one of the important factors in the success of a project. The analysis of the productivity of the tower crane in the Bintaro Jaya Xchange construction project phase II, aims to analyze the productivity of the tower crane in the Bintaro Jaya Xchange construction project phase II. This research was conducted by observing the daily volume and cycle time of 4 tower cranes. The results of calculations that have been carried out show that the average productivity of tower crane 1 is 8,069.66 kg/hour, tower crane 2 is 8,444.26 kg/hour, tower crane 4 is 7,504.84 kg/hour, and tower crane 5 is 8,524. ,17 kg/hour. From the results of the data above, it can be concluded that tower crane 5 has a higher average productivity compared to other tower cranes. This is because tower crane 5 has a strategic position so that it is more productive. For tower crane 4 has the lowest average productivity because in that zone no structural work has been carried out, so tower crane 4 only functions as a support for other tower cranes.